Security in the Era of Threats Occurring in Cyberspace - Bierecki, Dominik; Karpiuk, Mirosław; Melchior, Claudio; Strizzolo, Nicola (PRAWO i WIĘŹ, 2025)
Security has always been of paramount importance to both society and the state. In the era of widespread Internet access, we can speak of a new dimension related to the use of cyberspace. New threats are emerging that are not limited to specific countries but can even have an international dimension. Given that information and communication systems are now widely used around the world, cyberthreats that compromise their functioning are also common. New technologies, including artificial intelligence, are, on the one hand, a manifestation of the development of states and societies, but, on the other hand, if used improperly, they can lead to serious consequences, even disrupting the operation of strategic sectors and even necessitating the activation of crisis management mechanisms. When implementing and using information and communication technologies, the associated risks must also be considered. Electronically transmitted and shared information now occurs on a large scale, so it is crucial to avoid being manipulated.The purpose of this paper is to determine the security status of a digital state that utilises cyberspace for its operations. Within this state, society also benefits from new technologies, which are also based on cyberspace. This paper employs a dogmatic-legal approach and also includes a review of the literature. Therefore, qualitative methods related to text content analysis were used.